Supply Chain Performance Measurement Using the SCOR Model in a Public University Logistics Division - Gugun Gunawan; Ria Arifianti; Muhammad Rizal (Jurnal Ilmiah Manajemen Kesatuan, 2026)
In public-sector organizations, effective supply chain management is crucial to ensure operational efficiency and service reliability. Vendor performance and trust are key determinants of procurement success, yet systematic evaluations in higher education institutions remain limited. This study aims to measure supply chain performance in a public organization using the Supply Chain Operations Reference (SCOR) model, with vendor reliability serving as a proxy for supplier trust. A quantitative descriptive approach was employed, using secondary procurement data of consumable goods collected from the Logistics Division of Universitas Padjadjaran over 2022–2024. Performance indicators included on-time delivery, number of purchase orders, contract value, and annual reliability trends, which were aggregated into key performance indicators to assess vendor consistency and operational reliability. The results show that most vendors achieved on-time completion rates above 95 percent, reflecting very high operational reliability and stable service performance. Longitudinal analysis indicates a consistent pattern of reliability, suggesting that procurement planning, contract management, and performance monitoring have been effectively implemented. These findings confirm the applicability of the SCOR framework in evaluating public-sector supply chain performance and provide evidence supporting data-driven procurement governance and continuous performance improvement in higher education institutions.